Concerns of University Students Regarding COVID-19 Lockdown: An Online Cross-Sectional Survey in Karachi, Pakistan. - Seema Mumtaz, Sameera Ali Rizvi, Nida Shoaib, Ayesha Tahir, Niaz Ahmed, Sheikh Hassnain Haider, Mumtaz Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the concerns of university students regarding COVID-19 lockdown. Methods: A Cross-Sectional online survey was conducted among student population living in different socio-economical areas of Karachi. Information was gathered on their age, gender, education level, occupation status, area of residence, and knowledge about lockdown due to Covid-19. These variables were examined according to the socio-economic status of the area where students reside. Results: A total of 200 subjects above 20 years were interviewed out of which data was analyzed for 160 subjects. The majority of students were between the ages of 20-25 years, females, Muslims, and unemployed. According to 86.9% of students COVID-19 can be prevented by avoiding contact and almost 74.4% students were in favor of lockdown further 37.5% students wanted no gaps between lockdowns. In this study, 31.3% spent time using phones while 15% spent time reading while 22% of the students spent their time in physical activity. Almost 66.3% of students did not develop any psychological problems. About 77.5% did not face any financial problems. Conclusion: Most of the respondents were in favor of lockdown as COVID-19 spread can be prevented by avoiding contact. Study highlighted COVID-19 lockdown had no effect on mental health of the respondents. This study will help in creating awareness regarding lockdown. It will enlighten new arenas for public health experts and stakeholders to develop new strategies, and interventions and predict a preparedness program plan for future Pandemic. Keywords: Covid-19, severe acute respiratory syndrome (SARS), Lockdown, Karachi